Support Vector Machines - Christmann, Andreas; Steinwart, Ingo.; SpringerLink (Online service) (New York, NY : Springer New York, 2008)
This book explains the principles that make support vector machines (SVMs) a successful modelling and prediction tool for a variety of applications. The authors present the basic ideas of SVMs together with the latest developments and current research questions in a unified style. They identify three reasons for the success of SVMs: their ability to learn well with only a very small number of free parameters, their robustness against several types of model violations and outliers, and their computational efficiency compared to several other methods. Since their appearance in the early nineties, support vector machines and related kernel-based methods have been successfully applied in diverse fields of application such as bioinformatics, fraud detection, construction of insurance tariffs, direct marketing, and data and text mining. As a consequence, SVMs now play an important role in statistical machine learning and are used not only by statisticians, mathematicians, and computer scientists, but also by engineers and data analysts. The book provides a unique in-depth treatment of both fundamental and recent material on SVMs that so far has been scattered in the literature. The book can thus serve as both a basis for graduate courses and an introduction for statisticians, mathematicians, and computer scientists. It further provides a valuable reference for researchers working in the field. The book covers all important topics concerning support vector machines such as: loss functions and their role in the learning process; reproducing kernel Hilbert spaces and their properties; a thorough statistical analysis that uses both traditional uniform bounds and more advanced localized techniques based on Rademacher averages and Talagrand's inequality; a detailed treatment of classification and regression; a detailed robustness analysis; and a description of some of the most recent implementation techniques. To make the book self-contained, an extensive appendix is added which provides the reader with the necessary background from statistics, probability theory, functional analysis, convex analysis, and topology. Ingo Steinwart is a researcher in the machine learning group at the Los Alamos National Laboratory. He works on support vector machines and related methods. Andreas Christmann is Professor of Stochastics in the Department of Mathematics at the University of Bayreuth. He works in particular on support vector machines and robust statistics.
Loss Functions and Their Risks -- Surrogate Loss Functions (*) -- Kernels and Reproducing Kernel Hilbert Spaces -- Infinite-Sample Versions of Support VectorMachines -- Basic Statistical Analysis of SVMs -- Advanced Statistical Analysis of SVMs (*) -- Support Vector Machines for Classification -- Support Vector Machines for Regression. -- Robustness -- Computational Aspects -- Data Mining.
Keywords: Computer science; Mathematical statistics; Data mining; Artificial intelligence; Pattern recognition; Computer Science; Artificial Intelligence (incl. Robotics).; Probability and Statistics in Computer Science; Pattern Recognition; Data Mining and Knowledge Discovery; Signal, Image and Speech Processing; Electronic books